The Real-Time-Based Assessment of the Microbial Killing by the Antimicrobial Compounds of Neutrophils - J. T. Atosuo; E.-M. Lilius (The Scientific World Journal)
A recombinant Escherichia coli K-12 strain, transformed with a modified bacterial luciferase gene (luxABCDE) from Photorhabdus luminescens, was constructed in order to monitor the activity of various antimicrobial agents on a real-time basis. This E. coli-lux emitted, without any addition of substrate, constitutive bioluminescence (BL), which correlated to the number of viable bacterial cells. The decrease in BL signal correlated to the number of killed bacterial cells. Antimicrobial activity of hydrogen peroxide (H2O2) and myeloperoxidase (MPO) was assessed. In high concentrations, H2O2 alone had a bacteriocidic function and MPO enhanced this killing by forming hypochlorous acid (HOCl). Taurine, the known HOCl scavenger, blocked the killing by MPO. When E. coli-lux was incubated with neutrophils, similar killing kinetics was recorded as in H2O2/MPO experiments. The opsonization of bacteria enhanced the killing, and the maximum rate of the MPO release from lysosomes coincided with the onset of the killing.